(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
The use of arts to communicate and express values is seen in the cultural life across many African societies; they are symbolic and identify the people by narrating their customs, traditions and history. These arts are featured in the celebration of many festivals and some contribute to the level of reconciling people and resolving conflict. One popular festival in Ghana that is noted for using the arts as a symbolic role in resolving conflicts is the Apoo Festival, which is celebrated by the people of Techiman in the Brong Ahafo Region of Ghana. This study sought to investigate into these arts and how they are used as a symbolical aid during the Apoo Festival in resolving conflicts .Non-participant observation, personal interview, and focus group discussions guided the collection of data from 51 participants consisting of traditional authorities, traditional priests, elderly respondents, and the youth. The findings concludes that the use of arts as a symbolic element in aiding the Apoo Festival to project the message of peace to the community is indispensable.